2018
DOI: 10.1016/j.jenvman.2018.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Performance, microbial community and fluorescent characteristic of microbial products in a solid-phase denitrification biofilm reactor for WWTP effluent treatment

Abstract: Microbial products, i.e. extracellular polymeric substance (EPS) and soluble microbial product (SMP), have a significant correlation with microbial activity of biologically based systems. In present study, the spectral characteristics of two kinds of microbial products were comprehensively evaluated in a solid-phase denitrification biofilm reactor for WWTP effluent treatment by using poly (butylene succinate) (PBS) as carbon source. After the achievement of PBS-biofilm, nitrate and total nitrogen removal effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(9 citation statements)
references
References 49 publications
(51 reference statements)
0
9
0
Order By: Relevance
“…E x /E m = 230 nm/350 nm indicated the presence of a protein [ 28 , 29 ], likely a protein rich in tryptophan [ 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…E x /E m = 230 nm/350 nm indicated the presence of a protein [ 28 , 29 ], likely a protein rich in tryptophan [ 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Actinobacteria Actinobacteria includes some of the most common soil, freshwater and marine organisms that play important roles in the decomposition of organic substances (e.g., cellulose and xylan), thus in organic material turnover and carbon cycle. 29 Firmicutes can survive in certain extreme environments, and some species in the genus Firmicutes have heterotrophic nitrification, and in Li Yingying et al 30 Have shown that Firmicutes has some denitrification capacity. The relative abundance of Firmicutes was highest when the filling rate was increased to 40%, probably due to excessive discharge of excess sludge, resulting in selective enrichment of the microorganisms.…”
Section: Analysis Of the Colony Compositional Structure At The Phylum...mentioning
confidence: 99%
“…Decreasing HRT can increase the particle removal rate in the culture tank 38 and prevent water quality that compromises farmed animals' performance and welfare, 39 but it also increases the energy costs of the overall system. On the other hand, long HRT (2–24 h) can increase the nitrate‐N removal rate in bioreactor because it provides enough time for denitrification and thus significantly decrease the accumulation of nitrite 40,41 . However, it decreases the hydraulic load of the systems and reduces the sewage treatment capacity 42,43 .…”
Section: Infrastructure Of Land‐based Closed Aquaculture Systemsmentioning
confidence: 99%
“…On the other hand, long HRT (2-24 h) can increase the nitrate-N removal rate in bioreactor because it provides enough time for denitrification and thus significantly decrease the accumulation of nitrite. 40,41 However, it decreases the hydraulic load of the systems and reduces the sewage treatment capacity. 42,43 Considering all these constraints, improving the aquaculture environments by adjusting HRT cannot meet the demands for the sustainable development of aquaculture.…”
Section: Infrastructure Of Land-based Closed Aquaculture Systemsmentioning
confidence: 99%